Drug‐resistant epilepsy in adults: Outcome trajectories after failure of two medications. (6th June 2016) - Choi, Hyunmi; Hayat, Matthew J.; Zhang, Ruiqi; Hirsch, Lawrence J.; Bazil, Carl W.; Mendiratta, Anil; Kato, Kenneth; Javed, Asif; Legge, Alexander W.; Buchsbaum, Richard; Resor, Stanley; Heiman, Gary A.
Summary: Objective: To examine the seizure trajectories of adults with epilepsy developing drug‐resistant epilepsy (DRE) and to identify the predictors of seizure trajectory outcome. Methods: Adult patients failing two antiepileptic drugs (AEDs) due to inefficacy and starting their third AED at a tertiary epilepsy center were followed for seizure trajectory outcome during medical management. Seizure trajectories were categorized into one of four patterns: (1) course with constant seizures; (2) fluctuating course; (3) delayed attainment of seizure freedom (seizure freedom delayed for >12 months after start of the study, but patient stayed in seizure freedom); and (4) early attainment of seizure freedom (within 12 months of starting study). Multiple ordinal logistic regression models were used to estimate the association between trajectory categories and clinical factors. Results: Four hundred three adult patients met the eligibility criteria. Of these, 212 (53%) never achieved a seizure‐free period of a year or more. The trajectories of 63 patients (16%) had a complex fluctuating trajectory, 62 (15%) had delayed onset of seizure freedom, and 66 (16%) had an early seizure freedom. Independent predictors associated with more favorable outcome trajectories were epilepsy type and length of follow‐up. Specifically, compared to patients with focal epilepsy of temporal lobe, patients with focal epilepsy of occipital lobe (OR 3.80, 95% confidence interval [CI] 1.00–14.51, p = 0.04), generalized genetic (OR 3.23, 95% CI 1.88–5.57, p < 0.0001), unclear epilepsy type (OR 3.82, 95% CI 1.53–9.52, p < 0.005), and both focal and generalized epilepsy(OR 11.73, 95% CI 1.69–81.34, p = 0.01) were significantly more likely to experience a better trajectory pattern. Significance: Examination of patterns of seizure trajectory of patients with incident DRE showed that 31% were in continuous seizure freedom at the end of the observation period.